Stabilization of switched linear systems under asynchronous switching subject to admissible edge-dependent average dwell time - Hou, Linlin; Ma, Xuan; Sun, Haibin (Frontiers of information technology & electronic engineering, 2022)
The problem of stabilizing switched linear systems under asynchronous switching is addressed. The admissible edge-dependent average dwell time method is applied to design a switching signal that comprises slow admissible edge-dependent average dwell time and fast admissible edge-dependent average dwell time. Under this switching signal, the restriction that the maximum delay of asynchronous switching is known in advance is removed. The constructed Lyapunov function is associated with both the system mode and controller mode. The stabilization criteria and the corresponding algorithm are presented to obtain the controller gains and to design the switching signal. Finally, two examples are given to demonstrate the effectiveness of the proposed results.